PENGARUH KOORDINASI, KOMITMEN ORGANISASI DAN DISIPLIN KERJA TERHADAP EFEKTIFITAS KERJA KARYAWAN PT. BPR INDOMITRA MEGA KAPITAL PEKANBARU - Gatra, Martharezza Dwi; Nuryanti, Nuryanti; Pramadewi, Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. BPR Indomitra Mega Kapital Pekanbaru with the aim To know and analyze the influence of Coordination, Organizational Commitment and Work Discipline on the effectiveness of employee PT. RB Indomitra Mega Kapital Pekanbaru. This study uses primary data that is data obtained from interviews and giving questionnaires to all employees of PT. BPR Indomitra Mega Kapital Pekanbaru. Secondary data obtained related to the object and organizational structure of the population in this study were all employees who numbered 63 people and sampled. The method of analysis used in this study is multiple linear regression method. From the results of tests that have been done, simultaneous regression test (Test-F) shows that the variables Coordination, Organizational Commitment and Work Discipline simultaneously have a significant effect on Employee Effectiveness. From the results of partial tests (Test-t) indicates that the variables Coordination, Organizational Commitment and Work Discipline significantly influence Employee Effectiveness. The result of calculation of coefficient of determination (R2) is equal to 0,796 or equal to 79,6% which mean, Coordination variable, Organizational Commitment and Work Discipline together influence Effectiveness Employee, while the rest 20,40% influenced by other variables that not Investigated in this study.Keywords : Coordination, Organizational Commitment, Work Discipline and Work Effectiveness